Medicaid Expansion and the Mental Health of Spousal Caregivers - Joan Costa-Font; Nilesh Raut; Courtney H. Van Houtven (Review of Economics of the Household, 2023)
Abstract Health insurance expansions can exert wellbeing effects on individuals who provide informal care to their loved ones, reducing their experience of depression. This study exploits evidence from the Patient Protection and Affordable Care Act's Medicaid expansion (ACA Medicaid) to examine the effects on the mental wellbeing of informal caregivers . Drawing on an event study and a Difference-in-Differences (DID) design we investigate the policy impact of ACA Medicaid using longitudinal evidence (from the Health and Retirement Study, HRS) for low-income individuals aged 64 or below. We find that ACA Medicaid reduced the likelihood of depressive symptoms among spousal caregivers . We document that exposure to ACA Medicaid gives rise to 8.2% points (on average, equivalent to 30% decrease) reduction in the feeling of depression and 8.7% points increase in the feeling of happiness (on average, 11% increase). The estimates are robust to various specifications, are driven by reductions in out of -pocket expenses and labor supply and, as expected, increased after Medicaid uptake. The evidence from falsification tests confirms that the estimated effects are likely due to ACA Medicaid.
Keywords: 330